Oral GnRH Antagonists in Combination with Estradiol and Norethindrone Acetate for Pain Relief Associated with Endometriosis: A Review of Evidence of a Novel Class of Hormonal Agents - Othman ER; Al-Hendy A; Mostafa R; Lambalk CB; Mijatovic V (International Journal of Women's Health, 2024)
Essam R Othman,1,2 Ayman Al-Hendy,3 Radwa Mostafa,1 Cornelis B Lambalk,2 Velja Mijatovic2 1OB-GYN Department, Assiut University, Assiut, 71515, Egypt; 2Academic Endometriosis Center, Amsterdam University Medical Center, Vrije Universiteit Amsterdam, Amsterdam, the Netherlands; 3Department of Obstetrics and Gynecology, University of Chicago, Chicago, IL, 60637, USACorrespondence: Essam R Othman, Department of Obstetrics and Gynecology, Assiut University, Assiut, Egypt, Email essamothman@aun.edu.egAbstract: Current medical treatment options for endometriosis associated pains are inadequate. Evidence on effects of nonsteroidal anti-inflammatory drugs is scarce. Around one third of patients are not responsive to oral contraceptives or progestins due to progesterone resistance. Gonadotropin-releasing hormone (GnRH) agonists can only be used for a short duration because of associated side effects. Oral GnRH antagonists, including elagolix, relugolix, and linzagolix allow oral administration, induce dose dependent reduction of estradiol levels, do not cause initial flare up of endometriosis symptoms, and allow the fast return of ovarian function and menstruation after discontinuation. Elagolix at a low dose of 150 mg once daily, or the higher dose of 200 mg twice daily, significantly increased the proportion of women achieving clinically meaningful decline of dysmenorrhea, noncyclic pelvic pain, and dyspareunia. Relugolix at an oral dose of 40 mg/day results in improvement in different forms of endometriosis related pelvic pain, with an efficacy and side effect profile similar to that of GnRH agonists. Adding 1 mg of estradiol and 0.5 mg of norethindrone to 40 mg of relugolix (relugolix combination therapy) allows extension of treatment to 24 weeks with maintained efficacy and an improved side effect profile. Linzagolix, in a dose of 75 mg/day, can be used alone to treat endometriosis associated pain. For severe pelvic pain and dyspareunia, linzagolix can be used in a high dose of 200 mg/day with hormonal add-back therapy to preserve bone health.Plain Language Summary: Oral gonadotropin-releasing hormone (GnRH) antagonists, including elagolix, relugolix, and linzagolix, represent a new addition in the armamentarium against endometriosis associated pain. They are given orally, do not cause an initial flare-up of disease symptoms, allow a return of menses quickly after their withdrawal and produce a balance between ability to relieve endometriosis associated pain and side effects profile. The addition of hormonal agents like estradiol 1 mg and norethindrone acetate 0.5 mg to relugolix (relugolix combination therapy) allowed longer use of the medication for relief of endometriosis associated pain while reducing side effects like bone mineral density loss and hot flushes.Keywords: endometriosis, pain, elagolix, relugolix, linzagolix, estradiol, norethindrone